Cidades e globalização econômica : possibilidades de um regime urbano internacional - Tavares, Cesar (2016)
In a world of accelerated urbanization process, the issues related to social and environmental sustainability of cities are highlighted under international civil society. By the time the first international discussions on environment in Stockholm (1972), also the question of human settlements in urban centers has relevance in the international arena (Vancouver, 1976), putting the cities as a relevant theme in discussions of international civil society. Currently, there are networks of cities, international organizations, institutions, associations, foundations, anyway, a large international effort focused on urban problems. So, the hypothesis initially placed in this work is that all this international effort on urban problems could represent the establishment of an international urban regime. However, the answer to this question depends on the theoretical perspective to address urban problems. So were described two lines of reflection on urban problems: 1) the Group of liberal positions, composed of those who see in globalization (those who criticize and denounce the evils of global processes, or those who see economic and social advances with globalization) and the adaptation of cities to global flows a condition (to be leveraged or overcome) for sustainable development; 2) the Group of critical positions, from Marxist readings, which sees the incorporation of cities to global flows as a rearrangement of capitalist accumulation processes, leading to an extreme level the social inequalities and socio-spatial segregation in urban centers throughout the world. Connected to that cleavage of theoretical positions, it was possible to draw a parallel with another distinction between the international documents on human settlements, marked the position of the Vancouver Declaration (1976) and the World Charter for the Right to the City (2006), on the one hand, and of the Habitat Agenda (1996) position, on the other. The Vancouver Declaration and the Letter for the Right to the City highlights that the urbanization processes should be under exclusive civil service, being prohibited the transfer of decisions about the city to the private sector, emphasizing a citizen´s collective right to equal enjoyment of urban space and emphasizing too the property social function principle. Already the Habitat Agenda advocates a broad and extensive rights framework correlated to the city, seeking to cover all the views on urban problems, but always highlighting the role of the private sector (special feature of this document and main difference in relation to other statements) in the actions for implementation of these rights. Given by these theoretical divides, it can be concluded that international efforts aimed at institutionalizing an ""international urban regime"" can be identified as an effort of adaptation of cities to global economic flows, since the realization of the right to the city does not depend on a single global solution, but rather the satisfaction of specific conditions of each place, as well as the main role of citizens. On the other hand, international efforts can also be facing the other direction, that is, to make public the urban processes and to the spread of equitable distribution of burdens and benefits resulting from the construction of the urban space. In this sense, in conclusion, one can speak on global urban governance mechanisms, to strengthen the main role of citizens on the construction of the city and also the local initiatives for the realization of the right to the city.